Increasing the Turnover of MSMEs in Healthy Beverages Through Digital Marketing Strategies: A Case Study of Shuguci and WHF MSMEs - Dr. Mochamad Teguh Kurniawan, ST., MT; Fadilah, Samia (RAM PUBLISHER, 2025)
This study aims to analyze the effectiveness of applying Digital Marketing strategies in increasing the revenue and brand awareness of the Healthy Beverage MSMEs, Shuguci and WHF. The method used is qualitative with a case study approach, where data were collected through observation, in-depth interviews, and documentation of the MSMEs' digital marketing activities.The results show that after the mentoring program, the MSMEs' revenue increased by 50%, accompanied by improved understanding among owners and employees regarding digital marketing strategies. They are now more adept at using hashtags, determining optimal posting times, segmenting markets, and utilizing trending music in digital content. Additionally, customer interaction significantly improved, as indicated by the growing number of customers reaching out via direct messages during promotions and actively participating in live sessions on social media. The referral program offering discounts to customers who recommended the products also proved effective in increasing the number of new customers. It can be concluded that implementing Digital Marketing strategies can be an effective solution for MSMEs to increase their revenue and brand awarene